VDAC–Tubulin, an Anti-Warburg Pro-Oxidant Switch - Maldonado, Eduardo N. (Frontiers in Oncology, 2017)
Aerobic enhanced glycolysis characterizes the Warburg phenotype. In cancer cells, suppression of mitochondrial metabolism contributes to maintain a low ATP/ADP ratio that favors glycolysis. We propose that the voltage dependent anion channel (VDAC) located in the mitochondrial outer membrane is a metabolic link between glycolysis and oxidative phosphorylation in the Warburg phenotype. Most metabolites including respiratory substrates, ADP and Pi enter mitochondria only through VDAC. Oxidation of respiratory substrates in the Krebs cycle generates NADH that enters the electron transport chain (ETC) to generate a proton motive force utilized to generate ATP and to maintain mitochondrial membrane potential (ΔΨ). The ETC is also the major source of mitochondrial reactive oxygen species (ROS) formation. Dimeric α-β tubulin decreases conductance of VDAC inserted in lipid bilayers and high free tubulin in cancer cells, by closing VDAC, limits the ingress of respiratory substrates and ATP decreasing mitochondrial ΔΨ. VDAC opening regulated by free tubulin operates as a “master key” that “seal-unseal” mitochondria to modulate mitochondrial metabolism, ROS formation and the intracellular flow of energy. Erastin, a small molecule that binds to VDAC and kills cancer cells, and erastin-like compounds antagonize the inhibitory effect of tubulin on VDAC. Blockage of the VDAC-tubulin switch increases mitochondrial metabolism leading to decreased glycolysis and oxidative stress that promotes mitochondrial dysfunction, bioenergetic failure and cell death. In summary, VDAC-opening dependent cell death follows a “metabolic double hit model” characterized by oxidative stress and reversion of the pro-proliferative Warburg phenotype.